Deep plowing improves soil physical structure and alters nitrogen-cycling microbial communities in a subtropical red soil region - Li, Xiangyun; Liu, Yinuo; Pu, Yongyu; Shen, Guangcai; Gao, Siman; Kuang, Shuai; Song, Wenjing; Cong, Ping (Frontiers in Microbiology, 2026)
IntroductionTillage depth plays a critical role in regulating soil structure, nutrient dynamics, and microbial processes that determine crop productivity and quality.MethodsA 3-year field experiment was conducted in a subtropical red soil region to evaluate the effects of rotary tillage (RT), deep tillage with middle depth (DTM), and deep plowing (DP) on soil physicochemical properties, enzyme activities, microbial biomass, and nitrogen-cycling microbial communities.Results and discussionResults showed that RT significantly enhanced soil organic carbon, total nitrogen, available phosphorus, and microbial biomass across both 0–20 cm and 20–40 cm layers. In contrast, DP promoted higher nitrate levels, particularly in subsoils, and significantly enhanced ammonia-oxidizing bacteria (AOB) diversity in the tillage layer. Soil enzyme activities showed depth-dependent responses, with RT maintaining greater cellulase and urease activity compared to other treatments. Ammonia-oxidizing archaea (AOA) and AOB communities exhibited distinct compositional and diversity shifts under different tillage regimes, driven by soil nutrient availability, bulk density, and enzymatic activity. Co-occurrence network analysis further revealed that DTM and DP increased the complexity of AOA networks, while RT promoted higher connectivity and modularity in AOB networks. Additionally, DP significantly increased the proportion of superior-grade leaves compared to RT. Path analysis further clarified soil microbial biomass as the strongest positive direct driver of production benefits, mediating the effects of soil physicochemical and nutrient properties on crop value. These findings indicate that deep plowing boosts agricultural economic returns by optimizing the soil environment to enhance crop quality; however, to offset accelerated organic matter decomposition, integrating deep plowing with organic amendments is recommended for sustainable production.